An Enjoyment That Is Not Enjoyed: Simmel on the Dialectics of the Money-Form - Bueno, Arthur (Simmel Studies)

(untitled) (Edizioni ETS, 2025)
This article examines Simmel’s dialectics of the money-form by reconstructing his account of “hypertrophied” behaviours in the Philosophy of Money – greed, avarice, squandering, ascetic poverty, cynicism, and the blasé attitude. Developing his earlier diagnosis of the colonisation of ends by means, Simmel shows how the money-form is structurally marked by an “abstract form of enjoyment which, none the less, is not enjoyed”. Read as successive and ultimately failed attempts to secure an ultimate purpose within a money-mediated culture, these hypertrophied behaviours displace the tension between means and ends only to reproduce it in new registers, such that each apparent resolution yields renewed dissatisfaction. By foregrounding the peculiarity of Simmel’s tragic, non-reconciliatory dialectic in contrast to dialectical models oriented towards sublation, the article concludes by indicating how his account prefigures later diagnoses of social and subjective regression in critical theory.